Species Diversity, Molecular Phylogeny, and Ecological Habits of Fomitopsis (Polyporales, Basidiomycota) - Liu, Shun; Song, Chang-Ge; Xu, Tai-Min; Ji, Xing; Wu, Dong-Mei; Cui, Bao-Kai (Frontiers in Microbiology, 2022)
Fomitopsis is a worldwide brown-rot fungal genus of Polyporales, which grows on different gymnosperm and angiosperm trees and has important ecological functions and economic values. In this study, species diversity, phylogenetic relationships and ecological habits of Fomitopsis were investigated. A total of 195 specimens from 24 countries representing 29 species of Fomitopsis were studied. Based on the morphological characters and phylogenetic evidence of DNA sequences including the internal transcribed spacer (ITS) regions, the large subunit of nuclear ribosomal RNA gene (nLSU), the small subunit of nuclear ribosomal RNA gene (nSSU), the small subunit of mitochondrial rRNA gene (mtSSU), the translation elongation factor 1-α gene (TEF) and the second subunit of RNA polymerase II (RPB2), 30 species are accepted in Fomitopsis, including four new species, F. resupinata, F. srilankensis, F. submeliae and F. yimengensis. Illustrated descriptions of the novel species and the geographical locations of the Fomitopsis species are provided.